Motivation to learn in Madrasah ARRIDHA students - Rijal Arham Ahmad (Yayasan Ilomata, 2021)
Learning outcomes are often linked to the quality of education. If students get learning results with good grades. Then the teaching and learning process that lasts for that long is considered to have reached the minimum completeness criteria. Learning outcome is an evaluation of learning. The purpose of the evaluation is to find out information about the students' mastery of the material. How big is the student's motivation to learn at home during a pandemic? The author uses a survey method in this study. The magnitude of the influence of student learning motivation on student learning outcomes MI ARRIDHA Jakarta, is proven by statistical calculations which show the correlation coefficient (r) = 0.821. Efforts and efforts are needed in order to improve learning outcomes by making improvements to the student learning motivation variables that are carried out at the school concerned.